We Are Very Similar but Not Really: The Moderating Role of Cultural Identification for Refugee Resettlement of Venezuelans in Colombia - Ayala, Yarid; Bayona, Jaime Andrés; Karaeminogullari, Aysegul; Perdomo-Ortíz, Jesús; Ramos-Mejía, Mónica (Frontiers in Psychology, 2020)
In this study aims to test the theoretical model of career adaptability of refugees to investigate the dynamics of successful resettlement. The theoretical model is grounded on career construction and social network theory. We employ quantitative and qualitative methodologies to test the model in a sample of Venezuelans living and working in Colombia. The quantitative results provide partial support for Campion’s model. However, we test an alternative model and find that career adaptability has a direct relationship with subjective resettlement (i.e., life satisfaction and psychological health). In addition, cultural identification plays a buffering role on the harmful effects of discrimination on subjective resettlement. Qualitative results from eight in-depth interviews shed light on the process of refugee resettlement, thus revealing the role of social networks. Our study contributes to previous research on refugees by testing, adapting, and expanding a novel model of work resettlement and focusing on a group of refugees transitioning from one emerging country to another emerging country.